Calcium Channel Antagonists for Mood Disorders. Issue 2 (21st March 2022) - Dubovsky, Steven L.; Marshall, Dori
Abstract: Purpose: Development of new thymoleptic medications has primarily centered on anticonvulsants and antipsychotic drugs. Based on our studies of intracellular calcium ion signaling in mood disorders, we were interested in the use of novel medications that act on this mechanism of neuronal activation as potential mood stabilizers. Method: We reviewed the dynamics of the calcium second messenger system and the international body of data demonstrating increased baseline and stimulated intracellular calcium levels in peripheral cells of patients with bipolar mood disorders. We then examined studies of the effect of established mood stabilizers on intracellular calcium ion levels and on mechanisms of mobilization of this second messenger. After summarizing studies of calcium channel blocking agents, whose primary action is to attenuate hyperactive intracellular calcium signaling, we considered clinical experience with this class of medications and the potential for further research. Findings: Established mood stabilizers normalize increased intracellular calcium ion levels in bipolar disorder patients. Most case series and controlled studies suggest an antimanic and possibly mood stabilizing effect of the calcium channel blocking medications verapamil and nimodipine, with fewer data on isradipine. A relatively low risk of teratogenicity and lack of cognitive adverse effects or weight gain suggest possible applications in pregnancy and in patients for whom these are considerations. Implications: Medications that antagonize hyperactive intracellular signaling warrant more interest than they have received in psychiatry. Further experience will clarify the applications of these medications alone and in combination with more established mood stabilizers.